IMPLEMENTASI PROGRAM TAHFIDZUL QUR’AN DALAM PENGUATAN KARAKTER DI PONDOK PESANTREN MAHASISWA AL-BAROKAH MALANG - Helwina Afkarina; Dzulfikar Rodafi; Muhammad Sulistiono (VICRATINA, 2021)
Al-Barokah Student Islamic Boarding School Malang is a boarding school that is here to provide solutions to students who are dominated by students, so that they can balance every activity and obligation that is mandated. The division of time and creativity of the students of the Al-Barokah Islamic Boarding School Malang in participating in compulsory boarding activities without neglecting other obligations such as lectures and teaching. The purpose of this study is to find out the implementation of the Tahfidzul Qur'an Program in Strengthening Character at the Al-Barokah Student Islamic Boarding School Malang and to find out the contribution of the Tahfidzul Qur'an program implementation in strengthening the character of students at the Al-Barokah Islamic Boarding School Malang. Researchers conducted research using qualitative research methods with the type of Case Study on all students who took part in the Tahfidzul Qur'an Program at the Al-Barokah Islamic Boarding School Malang, amounting to 110 students. Data analysis was carried out by data reduction, data presentation, and conclusion drawing. The results of the research are the implementation of the Tahfidzul Qur'an program at the Al-Barokah Student Islamic Boarding School, Malang, which has two structured and unstructured programs, while the structured program is the deposit at dawn and ba'da isya', Sima'an 3 Juz Bin- Nadzar, Sima'an Kubro 5 Juz Bil-Ghaib, Khataman Al- Qur'an. The unstructured programs are independent memorization and independent muraja'ah. The contribution of the implementation of the Tahfidzul Qur'an Program in strengthening character lies in changing the character of students in daily life, and having an impact on its application in this regard so that it can lead to religious attitudes, disciplined, and responsible.